3X3 Basketball Tournaments in Debrecen - Pfau, Christa; Kalán, János; Bács, Zoltán; Müller, Anetta; Bácsné Bába, Éva (International Journal of Engineering and Management Sciences, 2018)
Faster attacks, spin speed, increased adrenaline levels, vehement play. This is all about the 3X3 basketball. In Debrecen, the first 3X3 basketball matches were held in 2015, most of them did not even think that the sport would be popular in Hungary as well. Practically, from the start of the first minute, the games were played with great success. Following the successful settlement, the International Basketball Association immediately offered a 3-year contract to Debrecen. The purpose of our research was to examine the 3X3 basketball tournaments in Debrecen, which was analyzed using a questionnaire and an in-depth interview. 69% of the respondents participated in the 2016 and 2017 events, but only 37% attended the 3X3 basketball tournaments that were held for the first time in 2015. It can be stated that this trend is growing and the event is gaining popularity nationwide. Sponsors and sponsors covered every issue of the event so the event was free of charge over the years. 72% of fillers, however, are willing to spend money on a possible entry fee. In terms of revenue growth, the introduction of admission fees is unlikely to reduce interest. Up to 1200 seats have been filled up for the event every year. Therefore, it is not surprising that a lot of people would like to enjoy a higher auditorium with more space. The introduction of 4-point boundaries (3 points) for 3X3 matches would be a great opportunity to try the "little brother" of basketball in the 4-point so that it can be introduced in traditional basketball. Hungary became the pioneer of the sport due to the results of the Hungarian national team and the successful organization of sporting events.